1990
DOI: 10.1128/jb.172.1.437-445.1990
|View full text |Cite
|
Sign up to set email alerts
|

mprA, an Escherichia coli gene that reduces growth-phase-dependent synthesis of microcins B17 and C7 and blocks osmoinduction of proU when cloned on a high-copy-number plasmid

Abstract: Microcins B17 and C7 are plasmid-determined, peptide antibiotics produced by Escherichia coli when cells enter the stationary phase of growth. Microcinogenic strains are immune to the action of the microcin they synthesize. A well-characterized deficient-immunity phenotype is exhibited by microcin B17-producing cells in the absence of the immunity gene mcbG (M.C. Garrido, M. Herrero, R. Kolter, and F. Moreno, EMBO J. 7:1853-1862, 1988). A 14.6-kilobase-pair EcoRI chromosomal fragment was isolated by its abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…The mprA (emrR) gene that is adjacent to emrA has a typical putative rho-independent terminator and was ascribed the function of regulating expression of microcin synthesis (4). The use of lacZ fusions to systematically search for the promoter of the operon led to the unexpected finding that emrR was actually a part of the emrAB operon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mprA (emrR) gene that is adjacent to emrA has a typical putative rho-independent terminator and was ascribed the function of regulating expression of microcin synthesis (4). The use of lacZ fusions to systematically search for the promoter of the operon led to the unexpected finding that emrR was actually a part of the emrAB operon.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that expression of emrAB can be induced by CCCP. We report here that the emrAB transcription initiates from the regulatory region of a previously described gene, mprA (4), that the expression of emrAB can be induced by several structurally unrelated compounds, and that mprA encodes a repressor of the pump synthesis. Some of the chemicals that induce this operon serve as substrates for the pump.…”
mentioning
confidence: 99%
“…A). A prototypic member of the entire regulator family is MarR, a repressor of the marROAB operon mediating intrinsic multiple antibiotic resistance in E. coli (17,18). To date, the crystal structures of three MarR-like proteins have been determined without their DNA targets.…”
mentioning
confidence: 99%
“…All of these effects appeared to be exerted at the transcriptional level. On the basis of these data and other evidence, we proposed that the mprA gene product (19 kDa) could play a regulatory role in the transcription of several E. coli genes (5). To further characterize mprA and to assess its presumed regulatory effects, we have examined the expression of mcb, mcc, and proU operons in null mprA mutants.…”
mentioning
confidence: 99%
“…A 742-bp DNA fragment containing mprA was sequenced by the dideoxy chain termination method (27). We took advantage of the collection of mprAlacZ fusions, generated by the insertion of the miniMudII1681 transposon (5) (Fig. 1A), to obtain convenient fragments to be sequenced.…”
mentioning
confidence: 99%